Audio Augmented Reality in Telecommunication through Virtual Auditory Display - Gamper, H.; Lokki, T.; Gamper, Hannes (Proceedings of the International Conference on Auditory Display (ICAD), 2010)
Audio communication in its most natural form, the face-to-face conversation, is binaural. Current telecommunication systems often provide only monaural audio, stripping it of spatial cues and thus deteriorating listening comfort and speech intelligibility. In this work, the application of binaural audio in telecommunication through audio augmented reality (AAR) is presented. AAR aims at augmenting auditory perception by embedding spatialised virtual audio content. Used in a telecommunication system, AAR enhances intelligibility and the sense of presence of the user. As a sample use case of AAR, a teleconference scenario is devised. The conference is recorded through a headset with integrated microphones, worn by one of the conference participants. Algorithms are presented to compensate for head movements and restore the spatial cues that encode the perceived directions of the conferees. To analyse the performance of the AAR system, a user study was conducted. Processing the binaural recording with the proposed algorithms places the virtual speakers at fixed directions. This improved the ability of test subjects to segregate the speakers significantly compared to an unprocessed recording. The proposed AAR system outperforms conventional telecommunication systems in terms of the speaker segregation by supporting spatial separation of binaurally recorded speakers.